Game-changing solutions for transforming Africa’s food systems: Successful cases - African Union Development Agency-NEPAD; Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report provides successful cases showcasing game-changing solutions for transforming Africa's food systems. The report starts by describing the failing state of food security and nutrition in Africa. It highlights recent action on food systems including the 2021 United Nations Food Systems Summit (UNFSS) dialogues and the associated Africa Common Position on Food Systems which presents several game-changing solutions for food systems transformation. It also presents other overarching and cross-cutting continental strategies and action plans that have been developed since the UNFSS and provides food system transformation accelerators for the national level. The last section of the report draws upon literature to provide a selection of African cases where game-changing interventions have successfully contributed (or have considerable potential to contribute) to food systems transformation.